DNAJB8 facilitates autophagic‐lysosomal degradation of viral Vif protein and restricts HIV‐1 virion infectivity by rescuing APOBEC3G expression in host cells. Issue 3 (1st February 2023) - Chand, Kailash; Barman, Muneesh Kumar; Ghosh, Payel; Mitra, Debashis
Abstract: HSP40/DNAJ family of proteins is the most diverse chaperone family, comprising about 49 isoforms in humans. Several reports have demonstrated the functional role of a few of these isoforms in the pathogenesis of various viruses, including HIV‐1. Our earlier study has shown that several isoforms of HSP40 get significantly modulated at the mRNA level during HIV‐1 infection in T cells. To explore the biological role of these significantly modulated isoforms, we analyzed their effect on HIV‐1 gene expression and virus production using knockdown and overexpression studies. Among these isoforms, DNAJA3, DNAJB1, DNAJB7, DNAJC4, DNAJC5B, DNAJC5G, DNAJC6, DNAJC22, and DNAJC30 seem to positively regulate virus replication, whereas DNAJB3, DNAJB6, DNAJB8, and DNAJC5 negatively regulate virus replication. Further investigation on the infectivity of the progeny virion demonstrated that only DNAJB8 negatively regulates the progeny virion infectivity. It was further identified that DNAJB8 protein is involved in the downregulation of Vif protein, required for the infectivity of HIV‐1 virions. DNAJB8 seems to direct Vif protein for autophagic‐lysosomal degradation, leading to rescue of the cellular restriction factor APOBEC3G from Vif‐mediated proteasomal degradation, resulting in enhanced packaging of APOBEC3G in budding virions and release of less infective progeny virion particles. Finally, our results also indicate that during the early stage of HIV‐1 infection, enhanced expression of DNAJB8 promotes the production of less infective progeny virions, but at the later stage or at the peak of infection, reduced expression of DNJAB8 protein allows the HIV‐1 to replicate and produce more infective progeny virion particles.